The usage of application R in historical studies on the example the analysis of youth letters of the 1920s - R. V. Rybakov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the problem of applying methods of quantitative analysis and specialized computer programs for statistical computations and graphical interpretation of results in historical studies. The possibilities of the R (R Project for Statistical Computing) application in analyzing the content of a historical source are shown. A factorial correlation analysis of the letters of youth of the 1920s is carried out. As a result of the application of the method of main components, the main causes that contributed to the spread of nonconformism among the youth of the period under study are established